2013
DOI: 10.1371/journal.pone.0067061
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Contribute to Sediment Nutrient Release and Reflect Progressed Eutrophication-Driven Hypoxia in an Organic-Rich Continental Sea

Abstract: In the sedimental organic matter of eutrophic continental seas, such as the largest dead zone in the world, the Baltic Sea, bacteria may directly participate in nutrient release by mineralizing organic matter or indirectly by altering the sediment’s ability to retain nutrients. Here, we present a case study of a hypoxic sea, which receives riverine nutrient loading and in which microbe-mediated vicious cycles of nutrients prevail. We showed that bacterial communities changed along the horizontal loading and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(68 citation statements)
references
References 89 publications
7
61
0
Order By: Relevance
“…During the November, February, May and August, the relative abundance of most of the predominant groups showed different patterns of variation in the sites 16 (heavy bloom area), 24 (light bloom area or macrophylic area) and 7 (mediate bloom area), implying they may play different ecologic functions in the sediments. These changes might be related to the responds of these bacteria to the nutrient conditions of the sediments during different bloom stages, since they have been described as the degraders of organic nutrient in marine sediment (Sinkko et al 2013). Our results demonstrated that the Alphaproteobacteria were more abundant during the algal bloom, which is similar to the findings elsewhere (Eiler et al 2006;Shao et al 2011;Ye et al 2009).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…During the November, February, May and August, the relative abundance of most of the predominant groups showed different patterns of variation in the sites 16 (heavy bloom area), 24 (light bloom area or macrophylic area) and 7 (mediate bloom area), implying they may play different ecologic functions in the sediments. These changes might be related to the responds of these bacteria to the nutrient conditions of the sediments during different bloom stages, since they have been described as the degraders of organic nutrient in marine sediment (Sinkko et al 2013). Our results demonstrated that the Alphaproteobacteria were more abundant during the algal bloom, which is similar to the findings elsewhere (Eiler et al 2006;Shao et al 2011;Ye et al 2009).…”
Section: Discussionsupporting
confidence: 88%
“…The sediments are the reservoir of nutrients for the water body and the sediment microorganisms drive the nutrient interchange between sediment and water which affects the trophic level of the water body (Sinkko et al 2013). The important roles of sediment microbes in energy and matter transformation in aquatic environments have been reported previously (Boyle-Yarwood et al 2008;Glissman et al 2004;Schmalenberger et al 2008;Tamaki et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The pH, DO, and E h were recorded by a calibrated Myron L Ultrameter (Myron L Company) in situ. Fresh sediment samples were cultured aerobically in 250-ml flasks for 2 weeks at 28°C with the addition of 200 ppm NH 4 ϩ -N; concentrations of NO 3 Ϫ -N were measured before and after the incubation to determine the sediment nitrification potential (56). The sediment denitrification potential was estimated through anaerobic incubation at 28°C for 3 days in sealed 250-ml flasks filled with N 2 ; the consumption of NO 3 Ϫ was calculated with an initial addition of 50 ppm NO 3 Ϫ -N (57).…”
Section: Methodsmentioning
confidence: 99%
“…Rapid and significant changes in the structure and functions of freshwater and marine ecosystems caused by humaninduced disturbances are of major concern (3). Nutrient cycles and pollutant clearing up in freshwater ecosystems mainly occur in the sediment surface layer through biological metabolic processes (4,5). The microbial communities can be responsible for 76% to 96% of the total sediment respiration, and the communities are generally known as a dominant driving force in the transformation of complex organic compounds (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation